Effect of Teaching Method on Exercise Execution in Adolescents' Use of Outdoor Fitness Equipment. Issue 4 (August 2022) - Gutiérrez-Santiago, Alfonso; Paramés-González, Adrián; Prieto-Lage, Iván
The use of outdoor fitness equipment (OFE) is an effective strategy to promote physical activity. The equipment normally includes information panels with phrases and images describing appropriate exercises. However, as using this equipment inappropriately is a potential problem, it is important to find an optimal unsupervised instruction method for correct exercise execution. Our objective in this study was to determine which of several exercise prescription methods, without direct professional supervision, might best instruct adolescents to correctly engage in upper limb motor execution on outdoor flexion-extension equipment. A total of 54 adolescents from a middle socioeconomic level in northwest Spain participated in this descriptive and quasi-experimental study. We randomly assigned members of this convenience sample into three groups who received either video instruction, instruction via images or written panel instructions. We used observational methodology in videographic analysis to evaluate the mistakes participants made in motor execution with each instructional method. We utilized different analytic techniques from observational methodology: statistical analyses (means, standard deviation, confidence intervals, ANOVA, etc.) and detecting T-Patterns with Theme and polar coordinate analysis using HOISAN. Participants who relied on video instructions committed fewer errors than those who relied on panel instructions. The video method prevented loss of information that occurred when instructional images were used. We suggest including a QR code on outdoor fitness equipment in open-air parks to permit users to download an explanatory video to their mobile phones.